Avaliação do uso de estufa solar para secagem de madeira serrada de eucalipto - Stangerlin, Diego Martins (2009)
This study aimed at evaluating the use of solar kiln for the drying of woods of Eucalyptus tereticornis, Eucalyptus saligna and Corymbia citriodora, as well as comparing the methodology to the air drying. In order to do so, it was built a solar kiln composed basically of wood structures, roofing with a double layer of PVC plastic, sunlight internal collector system and hot air circulation system. The efficiency of the solar kiln was compared to the air drying in the following aspects: time and drying tax, variation of the environmental conditions and wood quality resulting from the drying. The three eucalyptus species used in this experiment were obtained from homogeneous stands, and the cutting of logs into planks was tangential. In the same period of drying, each species was submitted to the two drying methods, being used a load with 60 boards in each method. Results indicated that the solar kiln had been more efficient as for time and drying tax. The time of drying in solar kiln was around 2 to 5 times faster than the air drying. Although the experiments were carried out in the winter, in low insolation and solar radiation, the drying in solar kiln presented satisfactory drying taxes, similar to those ones observed in more sophisticated solar kiln all over the world. Even when the conditions were not favorable to the air drying, the solar kiln presented higher temperatures and smaller indexes of moisture content and of equilibrium. The dried wood, in solar kiln and air drying, presented good quality, and no incidences like cup or collapse were verified. Furthermore, the correct piling up and drying process provided minimization of defects like bow. Despite the major occurrences of pieces with crook in solar kiln drying, the differences among the crook arrows, in the two drying methods, were insignificant. The incidence of end checking occurred from the drying in solar kiln was smaller in relation to the air drying only for woods of Eucalyptus tereticornis. On the other hand, the incidence of surface checks followed from the drying in solar kiln was inferior in comparison to the air drying process for the wood of Corymbia citriodora and Eucalyptus saligna.